HARVESTING AND PROCESSING OF NATIVE WOOD FROM UPLAND TROPICAL FORESTS IN AMAPÁ, EASTERN AMAZONIA - FIGUEIRA, CLAUDECILIA CHAVES DE OLIVEIRA; GUEDES, MARCELINO CARNEIRO; EULER, ANA MARGARIDA CASTRO (Floresta, 2020)
Knowledge about the activity of the timber sector and local industries assists in the management of a forest economy based on sustainable use in the Amazon. In this study, the situation of the timber sector of the municipality of Porto Grande-AP was examined to detail the extraction and processing of native wood from the Amazon and the sustainable use of this resource by the local sector. Forms were applied in all sawmills of the municipality, which collected information on factors of production and commercialization of native wood for the year 2017. In addition, interviews with local merchants were done and secondary data collection from several institutions related to the sector was conducted. All sawmills in the municipality exercise licensed activity and processed 69,300 m3 of wood in the period, with an average extraction of 21 m3/ha. The sawmills productive income was 55%, above of the 35%, maximum recently established by CONAMA. There is no destination for productive of residual waste generated by most sawmills and lumber is marketed mainly to the Northeast of Brazil for use in civil construction. Thus, in order to guarantee better economic and environmental performance of the sector, it is recommended that sawmills search for new forest areas as sources of raw material, participate in forest certification programs, and seek ways to use residual waste for bioenergy generation. The government recommends that new forests be managed through actions that solve land tenure problems and increase the supply of public forests, and for certified management units the recommendation is to reduce licensing costs, and simplify the bureaucratic processes of environmental agencies.